Temperature distribution in air tight cavities of steel framed modular buildings when exposed to fire - Bergroth, Elin; Torstensson, Greta (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2019)
A common way to construct large buildings is by assemble prefabricated modules around a load bearing steel construction. However, if a fire occurs these buildings can be subject to a rapid fire spread due to its cellular nature. By assembling modules side-by-side, gaps are created between the modules and these cavities must remain devoid of combustible material and remain air tight, even during fire. This to avoid that the air flow causes the cavities to work as “highways” for the fire spread which can lead to devastating damages. A Swedish example of a fire in a modular building is a residential building at Klintbacken, Luleå with a timber framed structure, which was constructed from prefabricated modules. The fire originated in a kitchen and spread through the cavities to several modular compartments and caused devastating damages on the construction. When buildings are constructed using a steel structure, high temperatures which occurs during a fire can cause the steel to lose its strength and stiffness. In some cases, unprotected steel members can resist fires without collapse, however to fulfil the fire resistance requirements the members do often need protection. To examine a steel structure in a modular building when exposed to fire, a fire test and temperature calculations have been performed and are presented in this thesis. The thesis is conducted in collaboration with Isolamin Sweden AB Part Group and consists of a fire test, theoretical calculations and a computer simulation using the finite element method. The aim of the thesis is to examine to what extent a steel column in a modular building is affected by a fire and to investigate the temperature distribution in the steel. For the fire test, a specimen consisted of a steel column and sandwich panels was created. The sandwich panels were assembled so that they created a cavity into where the steel column was placed. Temperature measuring devices such as thermocouples and a plate thermometer were placed on the specimen and a fire resistance furnace ...